Atividade antinociceptiva e anti-inflamatória do sesquiterpeno nerolidol em camundongos. - Fonsêca, Diogo Vilar da (2012)
Nerolidol, an acyclic sesquiterpene found as the major component in several essential oils, has antineoplastic, antimicrobial and antileishmanial activities, however its action in painful processes has never been studied. This study investigated the antinociceptive and anti-inflammatory activities of nerolidol in experimental pain and inflammation models in mice. On the pharmacological behavioral screening, the different doses tested by the nerolidol had psicodepressors behavioral changes such as decreased ambulation and analgesia. The LD50 could not be determined, since there were no deaths until the maximum dose of 2000 mg/kg. Motor coordination, evaluated through the rotarod test, was not altered in animals treated with nerolidol in any of the doses used. After, methods to evaluate the antinociceptive activity were used. Nerolidol reduced the number of acetic-acid induced abdominal contractions compared to the control group in all of the three doses tested. The formalin test, inhibited licking time both in the first phase (0 5 min) and in the second phase (15 30 min). Under the hot-plate test, nerolidol did not alter latency at any of the observed time-points. The mechanism of action of the antinociceptive property of nerolidol was assessed using the formalin test. The antinociception produced by nerolidol was significantly blocked in animals pre-treated with bicuculline (1 mg/kg, i.p.), indicating the involvement of GABAergic system. However, the effect of nerolidol was not reversed by the naloxone (non selective opioid antagonist, 5 mg/kg, s.c.) and glibenclamide (K +ATP channels bloker, 10 mg/kg, i.p.), demonstrating that at least directly, the nerolidol does not act by these mechanisms. The treatment with nerolidol was able to reduce the paw edemas induced by carragenina. At the model of peritonitis induced by carraggenan, nerolidol decreased the influx of leukocytes and also the levels of TNF-α in the peritoneal fluid. Therefore, these results indicate that nerolidol has antinociceptive activity with possible participation of the GABAergic system. Besides, nerolidol has anti-inflammatory activity that may be attributed to inhibition pro-inflammatory cytokines production TNF-α.